Case study as a research method - Zainal, Zaidah (Universiti Teknologi Malaysia, 2007)

(untitled)
Although case study methods remain a controversial approach to data collection, they are widely recognised in many social science studies especially when in-depth explanations of a social behaviour are sought after. This article, therefore, discusses several aspects of case studies as a research method. These include the design and categories of case studies and how their robustness can be achieved. It also explores on the advantages and disadvantages of case study as a research method.